2018
DOI: 10.1159/000487669
|View full text |Cite
|
Sign up to set email alerts
|

Gastritis Can Cause and Trigger Chronic Spontaneous Urticaria Independent of the Presence of <b><i>Helicobacter pylori</i></b>

Abstract: Background/Aim: In chronic spontaneous urticaria (CSU), Helicobacter pylori (HP) has been discussed as a cause, but it is unknown whether the bacterium itself or concomitant inflammation is causing the urticaria. Our aim was to investigate HP and upper gastrointestinal lesions as signs of inflammation independently of each other in the pathogenesis of CSU. Methods: A total of 36 prospectively enrolled CSU patients from Moscow were investigated by gastroscopy and screened for the presence of HP and/or upper gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 14 publications
0
12
0
1
Order By: Relevance
“…Among the 22 studies, a total of 1385 CSU patients, who were all assessed and diagnosed by dermatologists, were enrolled. The characteristics of the included studies are listed in Table .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Among the 22 studies, a total of 1385 CSU patients, who were all assessed and diagnosed by dermatologists, were enrolled. The characteristics of the included studies are listed in Table .…”
Section: Resultsmentioning
confidence: 99%
“…[40][41][42][43] Moreover, enhanced gastric permeability may also play a role; CSU is associated with a pseudo-allergy to food and increased permeability of the gastric mucosa, since damage caused by HP may give rise to inappropriate immunorecognition of food allergens. 6,44 Zheleznov et al 29 amounts may remain and regrow at a later time. 54 The test used to detect eradication does not guarantee full and complete elimination of all bacteria.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As blood levels of NO x and nitrate are significantly higher in CSU patients compared to healthy controls, and correlate with disease activity, a pathogenic role of nitrosative stress has been suggested [64]. A recent study reported a frequent association of CSU with upper gastrointestinal inflammatory disorders with and without Helicobacter pylori infection, and an improvement of urticaria in parallel with a successful treatment of the gastrointestinal disorder [65]. In India, H. pylori infections, which are mainly asymptomatic, are also frequent in CSU patients; however, the implications for disease course and severity are not clear [66].…”
Section: Unraveling Urticariamentioning
confidence: 99%